Development and Evaluation of Probiotic Based Bioinoculant for Enhancing Soil Fertility and Growth Variables in Triticum aestivum (Wheat) - Asmita Shinde; Aishwarya Pawar; Prathmesh Bhosale; Manasi Raut; Manisha Shinde (The Bioscan, 2025)
Modern agriculture focuses on enhancing crop yield to fulfill the food demands of a growing global population, mostly depend on the intensive application of chemical fertilizers and pesticides. However, the excessive use of these agrochemicals has been found as a major cause of the decline in microbial biodiversity, leading to reduced soil fertility, contamination of soil and water resources, and significant hazards to human and environmental health. Sustainable agricultural practices promote the use of microorganisms to enhance crop yield and soil health. Plant growth-promoting microorganisms play a pivotal role in sustainable agriculture by enhancing soil fertility and promoting plant growth through beneficial microbial interactions. The present work focuses on the development of bioinoculants derived from probiotic organisms isolated from dairy products such as curd and buttermilk. The isolated probiotics microbial strains, including Lactococcus cremoris subsp. tructae, Streptococcus lactaricus, and Lacticaseibacillus sharpeae were studied to determine their nitrogen fixation and phosphate solubilization ability. The efficacy of these probiotic microorganisms was evaluated through in vitro and field trials, where agronomic parameters including plant height, spike height, number of spikes, and grain yield were measured. Statistical analysis using the Mann-Whitney U test in Python was employed to determine the significance of the observed effects. The results demonstrated a significant enhancement in plant growth, indicating that probiotic-based bioinoculants offer a sustainable, eco-friendly alternative to chemical fertilizers. This study highlights the potential of probiotic microorganisms isolated from fermented dairy products in improving crop productivity and soil health within the framework of sustainable agriculture.